The Urban Village, Agrarian Transformation, and Rentier Capitalism in Gurgaon, India. Issue 5 (30th July 2018) - Cowan, Thomas
Abstract: Gurgaon, India's "millennium city", is today synonymous with India's embrace of global real estate capital and private sector‐led urban development. This paper asserts that Gurgaon's spectacular urbanisation has been fundamentally underpinned by an uneven process of land acquisition, exemption and agrarian transformation. Shifting away from dispossession‐centred analyses of contemporary urbanisation in India, this paper explores Gurgaon's "urban villages" to consider the uneven integration of agrarian classes into emerging urban real estate markets. Through an examination of differential experiences of land acquisition and agrarian social change among Gurgaon's landowning classes, the paper seeks to trace complex and nonlinear processes of agrarian transformation which make possible landscapes of global accumulation.